Initial denaturing conditions influence the slow folding phase of acylphosphatase associated with proline isomerization. - Pertinhez, T; Hamada, D; Smith, L; Chiti, F; Taddei, N; Stefani, M; Dobson, C (2000)
The folding kinetics of human common-type acylphosphatase (cAcP) from its urea- and TFE-denatured states have been determined by stopped-flow fluorescence techniques. The refolding reaction from the highly unfolded state formed in urea is characterized by double exponential behavior that includes a slow phase associated with isomerism of the Gly53-Pro54 peptide bond. However, this slow phase is absent when refolding is initiated by dilution of the highly a-helical denatured state formed in the presence of 40% trifluoroethanol (TFE). NMR studies of a peptide fragment corresponding to residues Gly53-Gly69 of cAcP indicate that only the native-like trans isomer of the Gly-Pro peptide bond is significantly populated in the presence of TFE, whereas both the cis and trans isomers are found in an approximately 1:9 ratio for the peptide bond in aqueous solution. Molecular modeling studies in conjunction with NMR experiments suggest that the trans isomer of the Gly53-Pro54 peptide bond is stabilized in TFE by the formation of a nonnative-like hydrogen bond between the CO group of Gly53 and the NH group of Lys57. These results therefore reveal that a specific nonnative interaction in the denatured state can increase significantly the overall efficiency of refolding.